Bone marrow mesenchymal stem cells attenuate silica-induced pulmonary fibrosis via paracrine mechanisms. (15th March 2017) - Li, Xiaoli; Wang, Yan; An, Guoliang; Liang, Di; Zhu, Zhonghui; Lian, Ximeng; Niu, Piye; Guo, Caixia; Tian, Lin
Graphical abstract: BMSCs attenuated silica-induced pulmonary fibrosis and reduced the injury of alveolar epithelial. The therapeutic effects of BMSCs might be associated with paracrine effect rather than differentiation. Highlights: BMSCs attenuat silica-induced fibrosis and reduce the injury of alveolar epithelial in vivo and in vitro. BMSCs do not differentiate into alveolar epithelial cells. The effects of BMSCs might be associated with paracrine rather than differentiation. Abstract: The purpose of this study was to investigate the anti-fibrotic effect and possible mechanism of bone marrow mesenchymal stem cells (BMSCs) in silica-induced lung injury and fibrosis in vivo and in vitro. In vivo, rats were exposed to 50 mg/ml silica intratracheally. The rats were sacrificed on day 15 or day 30 after intravenous injection of BMSCs. Histopathological examination demonstrated that BMSCs decreased the blue areas of collagen fibers and the number of nodules. Alveolar epithelium was damaged by silica, but it was restored by BMSCs. In vitro, BMSCs co-cultured with RLE-6TN cells in 6-Transwell plates were evaluated to determine the possible mechanism. The results demonstrated that BMSCs downregulated the expression of collagen I and III. BMSCs reversed morphological abnormalities and reduced the proliferation of RLE-6TN cells. These data showed that BMSCs did not give rise to alveolar epithelial cells directly, while the levels of hepatocyte growth factor, keratinocyte growth factor and bone morphogenetic protein −7 increased and expression of tumor necrosis factor-α and transforming growth factor-β1 decreased in the 6TN + Silica + BMSCs group compared with the 6TN + Silica group. Our results revealed that BMSCs exerted anti-fibrotic effects on silica-induced pulmonary fibrosis, which might be associated with paracrine mechanisms rather than differentiation.